LOW BACK PAIN AMONG SAMARINDA SARONG'S TRADITIONAL WEAVERS AND ITS RELATED FACTORS - Ramdan, Iwan Muhamad; Sartika, Dewi (Public Health of Indonesia, 2019)
Background: Low back pain (LBP) is a type of musculoskeletal disorder that has a detrimental effect on both workers and business continuity. Weaving activities with handloom are at risk for this disorder.Objective: To analyze the prevalence of LBP among Samarinda sarong's traditional weavers and its related factors.Methods: A cross sectional study was conducted on 49 traditional weavers of Samarinda Sarong. The instruments included the Owestry low back pain disability questionnaire, rapid entire body assessment (REBA), microtoise staturmeter and stopwatch. Data were analyzed using multiple logistic regressions.Results: The result showed that most of the weavers (92.5%) experienced LBP. Age (p= .000), work experience (p=.000), workload (p=.048) and work posture (p=.000) were significantly associated with LBP, while nutritional status (p=.773) and workload (p= .343) were not associated with LBP. Age and work posture were the most dominant variables affecting LBP.Conclusion: The prevalence of LBP among Samarinda sarong's traditional weavers was quite high and was strongly influenced by the weavers' age and posture work. In order to improve work posture and reduce the incidence of LBP, it is recommended to modify handlooms (tables and chairs) by following ergonomic rules, reducing workload, work time limitation and adequate rest.